1985
DOI: 10.1063/1.335737
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency calculations of thin-film GaAs solar cells on Si substrates

Abstract: Dislocation effect upon the efficiency of single-crystal thin-film AlGaAs-GaAs heteroface solar cells on Si substrates is analyzed. Solar-cell properties are calculated based on a simple model; in the model, dislocations act as recombination centers to reduce the minority-carrier diffusion length in each layer and increase the space-charge layer recombination current. Numerical analysis is also carried out to optimize thin-film AlGaAs-GaAs heteroface solar-cell structures. The fabrication of thin-film AlGaAs-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(83 citation statements)
references
References 11 publications
3
80
0
Order By: Relevance
“…This is in accord with the observations, wherein a correlation was found to exist between reverse leakage current density ͑J 0 ͒ and relative dislocation densities ͑N DIS ͒. Such a correlation is supportive of the above hypothesis, because J 0 is a function of minority-carrier lifetime, , in the space-charge region 2,16 and is dependent on N DIS as follows:…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This is in accord with the observations, wherein a correlation was found to exist between reverse leakage current density ͑J 0 ͒ and relative dislocation densities ͑N DIS ͒. Such a correlation is supportive of the above hypothesis, because J 0 is a function of minority-carrier lifetime, , in the space-charge region 2,16 and is dependent on N DIS as follows:…”
Section: Resultssupporting
confidence: 80%
“…Recent studies have shown that these effects manifest themselves in differing guises for a wide variety of devices, e.g., dislocations can reduce the current gain in AlGaAs/GaAs heterojunction bipolor transistors ͑HBTs͒, 1 and heteroepitaxial solar cells have low efficiencies due to misfit and thermally induced dislocations acting as recombination centers. [2][3][4] This article reports on the use of synchrotron x-ray topography ͑SXRT͒ to analyze the defect/dislocation distributions within wafer substrates and their correlation with substandard performance of GaAs power varactor diodes.…”
Section: Introductionmentioning
confidence: 99%
“…Other devices can also benefit from these materials, such as heterojunction bipolar transistors, 1.3 and 1.55 m photodetectors and lasers, and InP-onGaAs and GaAs-on-Si devices in general. Many research studies have investigated the promise of metamorphic materials for solar cells, [3][4][5][6][7][8][9][10][11] often citing 40% conversion efficiency as a possible goal. This letter reports on three-junction metamorphic and lattice-matched cells that have now surpassed the 40% efficiency milestone.…”
Section: % Efficient Metamorphic Gainp/ Gainas/ Ge Multijunction Somentioning
confidence: 99%
“…Consistent with the wide range of TDD's that have been reported for varying GaAs/Si integration approaches, a large variation in lifetime has been measured stemming from the epitaxial hurdles present in the GaAs/Si material system; namely, a 4% lattice mismatch and a nonpolar/polar interface. The influence of lattice mismatch on lifetime has been modeled as τ max represents the minority carrier lifetime in the absence of TDs and τ TDD represents the lifetime contribution resulting from recombination at TDs, which depends on D, on the minority carrier diffusion coefficient, and on the TDD (10,12). In one instance, minority carrier lifetime measurements facilitated using GaAs double heterostructures (DHs) grown on Si substrates via direct epitaxy using III-V strained-layer superlattices as interlayers have been reported to be up to 2 ns in n-type GaAs.…”
Section: Minority Carrier Lifetimementioning
confidence: 99%